Performance-related physiological changes induced by one year of endurance training in young athletes - Mishica, C.; Kyröläinen, H.; Valtonen, M.; Holmberg, H. C.; Linnamo, V. (Frontiers in Sports and Active Living, 2023)
Introduction: Although maximal oxygen uptake (VO2max) is generally recognized as the single best indicator of aerobic fitness in youth, interpretation of this parameter and the extent to which it can be improved by training remain controversial, as does the relative importance of VO2max for performance in comparison to other factors such as power production. Here, we examined the influence of endurance training on the VO2max, muscle power and sports-related performance of cross-country skiers attending a school specializing in sports, as well as potential relationships between any changes observed to one another and/or to perceived stress scale (Cohen) and certain blood parameters.